2022
DOI: 10.1021/acs.cgd.2c00204
|View full text |Cite
|
Sign up to set email alerts
|

trans-9,10-Dihydro-9,10-ethanoanthracene-11,12-dicarboxylic Acid: Complete Host Selectivity for Guest Compound para-Dichlorobenzene during Crystal Growth from Mixed Isomeric Dichlorobenzenes

Abstract: Here, we report on the results obtained when trans-9,10-dihydro-9,10-ethanoanthracene-11,12-dicarboxylic acid (DED) crystals were grown from mixtures containing equimolar isomeric o-, m-, and p-dichlorobenzenes (o-DCB, m-DCB, and p-DCB). DED displayed a remarkable affinity for p-DCB in both binary and ternary recrystallization experiments involving this guest species, and near-quantitative amounts of p-DCB were measured in the resultant crystals (96.4−100.0%). The host selectivity was in the order p-DCB >>> m-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…The strengths of these interactions were all comparable and significant, the respective O•••O distances ranging between 2.625(2) and 2.674(2) Å with associated angles between 172 and 178°. Notably, the unit cell dimensions of 2(DED)•4-BA are very similar to those of an analogous complex of DED with pdichlorobenzene from a previous report, 22 and the space groups are identical. As a result, the host molecule arrangements in the crystals of 2(DED)•4-BA and the 2:1 complex containing pdichlorobenzene are thus isostructural.…”
Section: Single Crystal X-ray Diffraction Experiments Tablesupporting
confidence: 75%
See 2 more Smart Citations
“…The strengths of these interactions were all comparable and significant, the respective O•••O distances ranging between 2.625(2) and 2.674(2) Å with associated angles between 172 and 178°. Notably, the unit cell dimensions of 2(DED)•4-BA are very similar to those of an analogous complex of DED with pdichlorobenzene from a previous report, 22 and the space groups are identical. As a result, the host molecule arrangements in the crystals of 2(DED)•4-BA and the 2:1 complex containing pdichlorobenzene are thus isostructural.…”
Section: Single Crystal X-ray Diffraction Experiments Tablesupporting
confidence: 75%
“…As examples, Nassimbeni et al employed a binaphthyl-derived host compound in order to separate the lutidine isomers, while Barbour and co-workers achieved xylene isomer separations with a Werner complex . In our own laboratories, we have also focused on these separation challenges and considered a wide variety of isomers, including the methylpyridines, xylenes and ethylbenzene, dichlorobenzenes, and anilines (as examples), by making use of host compounds synthesized from xanthone, thioxanthone, anthracene, and tartaric acid. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Interestingly, DED, when recrystallized from all possible combinations of equimolar mixtures of o-, m-, and p-dichlorobenzene (p-DCB), displayed a near-complete selectivity for the para isomer in every instance (in the present case, the para isomer was also the favored one). 25 In that work, it was shown that the complex containing this guest crystallized also in the triclinic crystal system and space group P1̅ , and a comparison of the unit cell dimensions revealed the host packing in 2(DED)•p-DCB to be isostructural with 2(DED)•4-MA.…”
Section: Assessment Of the Selectivity Behavior Of Ded In Binary Solu...mentioning
confidence: 94%
“…These encouraging observations stimulated a closer scrutiny of the behaviors of related molecules DED , H1 , and H2 in analogous experimental conditions. While the selectivity of various roof-shaped host compounds has been explored in mixed picolines, dichlorobenzenes (DCBs), and ethylbenzene/xylenes with remarkable selectivity data being obtained in these instances, the host behavior of DED , H1 , and H2 has not been assessed when presented with anisole mixtures. As such, here, successfully formed complexes were analyzed by both single-crystal X-ray diffraction (SCXRD) and thermal analyses to understand any selectivity displayed by these host compounds, to observe noncovalent interactions responsible for guest retention and also to investigate the relative thermal stabilities of the so-formed complexes.…”
Section: Introductionmentioning
confidence: 99%